Sejarah Tradisi Selapanan pada Masyarakat Jawa di Desa Pulau Tagor Kecamatan Serbajadi Kabupaten Serdang Bedagai - Khusna, Leli; Siregar, Yusra Dewi; Nasution, Kasron Muhsin (Asian Journal of Islamic Studies and Da'wah, 2023)
The history of the selapanan tradition in the tradition of the Javanese community which took place in the village of Pulau Tagor, Serbajadi District, Serdang Bedagai Regency and the Islamic view of the Selapanan tradition. The approach used is a cultural anthropological approach which is the view of life of a group of people in the form of behavior, beliefs, values and symbols that they receive unconsciously, all of which are passed down through a communication process from one generation to the next. The results show that the Selapanan tradition has existed since long ago in the Javanese region, and after the Javanese people from Central Java and its surroundings migrated to East Sumatra so that this tradition could develop and survive from generation to generation until it is still being carried out today. The Selapanan tradition has a good meaning as an expression of gratitude to Allah SWT. The Selapanan tradition procession is also permissible in Islam.